Factors Associated with the Level of Anemia in Third Trimester Pregnant Women in the Work Area of the Situmeang Habinsaran Community Health Center in 2020 - Naomi Isabella Hutabarat (Science Midwifery, 2021)
Anemia is a decrease in hemoglobin, hematocrit and erythrocyte count below normal values, which is less than 11 g / dl. The purpose of this study was to determine the factors associated with anemia in third trimester pregnant women in the work area of ​​the Situmeang Habinsaran Community Health Center in 2020. The design of this study was an analytical survey with a cross sectional approach. The population was 30 trimester III pregnant women. Sampling used was total sampling, the respondents were pregnant women in the third trimester who experienced anemia as many as 30 respondents. Based on the results of the analysis using the Chi Square test, it shows that the significant probability value (Asymp.Sig) is that there is a relationship between parity and anemia in pregnant women with a p-value = 0.003, there is a relationship between antenatal care in pregnant women with a p-value = 0.005. There is a knowledge relationship with anemia in pregnant women with a p-value = 0.011, there is a relationship between compliance with anemia in pregnant women with a p-value = 0.028. The conclusion in this study is that there is a relationship between parity, antenatal care, knowledge, adherence to taking Fe tablets with anemia in third trimester pregnant women. It is hoped that pregnant women should check their pregnancy and strive to frequently check their Hb and pay attention to the food consumed during pregnancy because healthy mothers do not necessarily have normal Hb levels.